Identification of DYNLT1 associated with proliferation, relapse, and metastasis in breast cancer - Miao, Sen; Ju, Gaoda; Jiang, Chonghua; Xue, Bing; Zhao, Lihua; Zhang, Rui; Diao, Han; Yu, Xingzhou; Zhang, Linlin; Pan, Xiaozao; Zhang, Hua; Zang, Lijuan; et al. (Frontiers in Medicine, 2023)
Background Breast cancer (BC) is the most common malignant disease in worldwide. Although the survival rate is improved recent years, the prognosis is still bleak once recurrence and metastasis occur. It is vital to investigate more efficiency biomarkers for predicting the metastasis and relapse of BC. DYNLT1 has been reported that participated in the progression of multiple cancers. However, it is still a lack of study about the correlation between DYNLT1 and BC. Methods In this study, we evaluated and validated the expression pattern and prognostic implication of DYNLT1 in BC with multiple public cohorts and BC tumor microarrays (TMAs) of paraffin-embedded tissues collected from Affiliated Hospital of Jining Medical University. The response biomarkers for immune therapy, such as tumor mutational burden (TMB) etc., between different DYNLT1 expression level BC samples were investigated using data from TCGA-BRCA cohort utilizing public online tools. In addition, colony formation and Transwell assay were conducted to verify the effects of DYNLT1 in BC cell lines proliferation and invasion. Results The results demonstrated that DYNLT1 overexpressed in BC and predicted poor relapse free survival in our own BC TMA cohort. As well, DYNLT1 induced BC development by promoting MDA-MB-231 cells proliferation migration, and metastasis. Conclusion Altogether, our finding proposed that DYNLT1 could be a diagnostic and prognostic indicator in BC.